The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.5713/ajas.2002.1288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementing Sheep with Sunflower Acid Oil or its Calcium Soap on Nutrient Utilization

Abstract: Four adult rams (22.25±0.90 kg) were used in a 4×4 latin square design to evaluate the rations without (T 1 ) or with supplementation of sunflower acid oil at 5 (T 2 ), 10 (T 3 ) or calcium soap at 10% of dietary DM (T 4 ) on nutrient digestibility and balances of nitrogen, calcium and phosphorus. The basal ration contained 60 parts Brazilian napier grass hay and 40 parts concentrate mixture. The DM, CF, NDF and ADF digestibilities and nitrogen retention (g/d) decreased (p<0.01) by inclusion of sunflower acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
(21 reference statements)
3
6
0
1
Order By: Relevance
“…The digestibility of fatty acid increases as unsaturation increases. Hence, the higher digestibility of EE and CP in RPF diets might be due to the lower ruminal biohydrogenetion and availability of large proportion of long chain unsaturated fatty acids in the small intestine for absorption [53].…”
Section: Discussionmentioning
confidence: 99%
“…The digestibility of fatty acid increases as unsaturation increases. Hence, the higher digestibility of EE and CP in RPF diets might be due to the lower ruminal biohydrogenetion and availability of large proportion of long chain unsaturated fatty acids in the small intestine for absorption [53].…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini menandakan bahwa penambahan minyak pada level 4% dalam bentuk bebas belum mengganggu kecernaan bahan pakan. Sebaliknya hasil penelitian Alexander et al (2002) menunjukkan bahwa penambahan 5% minyak bunga matahari dalam bentuk bebas secara in vivo pada pakan 60% hay Brazilian napier dan 40% konsentrat sangat nyata (P<0,01) menurunkan kecernaan bahan kering, Protein Kasar (PK) , NDF, ADF, hemiselulosa, dan s e l u l o s a d i b a n d i n gka n d e n ga n ko n t ro l ( t a n p a penambahan minyak). Penurunan kecernaan bahan pakan semakin meningkat dengan penambahan 10% kecernaannya, apabila KCBK meningkat tentu KCBO juga akan meningkat.…”
Section: Populasi Protozoa Dan Bakteri Rumenunclassified
“…Hill and West (1991) reported that supplementation with 4.5% of calcium soap did not significantly affect the digestibility of energy. However, supplementation with calcium soap significantly increased ( p > 0.05) the TDN, DE and ME contents of the diets supplemented with protected fat at the 10-15% level (Alexander et al, 2002;Ramana Reddy et al, 2003).…”
Section: Nutrient Digestibilitymentioning
confidence: 96%